2019
DOI: 10.1002/micr.30485
|View full text |Cite
|
Sign up to set email alerts
|

The thin profunda femoral artery perforator flap for tongue reconstruction

Abstract: Background With the ongoing global epidemic of obesity in the Western countries, thigh flaps such as the profunda artery perforator (PAP) free flap, have been less favorable for glossectomy reconstruction due to large bulk of adipose tissue associated with traditional subfascial harvest. In this article, we present a series of 10 patients who underwent reconstruction with suprafascial PAP free flaps following oncologic tongue resection. Methods Our series included six men and four women with an average age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 21 publications
0
30
1
Order By: Relevance
“…Accuracy was not adequate to measure long distances with changing axes. However, we have previously reported our series of thin PAP flaps for tongue reconstruction, with a mean pedicle length of 7.4 cm (range, 6–8 cm) (Heredero et al, 2019), and other authors have reported mean pedicle lengths ranging between 8 cm (Iida et al, 2019) and 10.3 cm (Haddock et al, 2017; Scaglioni et al, 2015). Another limitation is the lack of description of the venous anatomy.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Accuracy was not adequate to measure long distances with changing axes. However, we have previously reported our series of thin PAP flaps for tongue reconstruction, with a mean pedicle length of 7.4 cm (range, 6–8 cm) (Heredero et al, 2019), and other authors have reported mean pedicle lengths ranging between 8 cm (Iida et al, 2019) and 10.3 cm (Haddock et al, 2017; Scaglioni et al, 2015). Another limitation is the lack of description of the venous anatomy.…”
Section: Discussionmentioning
confidence: 81%
“…Bulky flaps assuring palatal‐glossal contact, such as the rectus abdominus (RA) and the anterolateral (ALT) free flaps, are among the most popular reconstructive options worldwide (Chepeha, 2010; Han et al, 2019). Recently, the profunda artery perforator (PAP) flap, harvested from the posteromedial region of the thigh, has been proposed as a good choice for tongue reconstruction (Fernández‐Riera et al, 2017; Heredero et al, 2019; Scaglioni et al, 2015; Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reviewed series of flaps dissected above the deep or the superficial fascia include preoperative imaging planning. Studies carried out by Heredero et al 37 with CT-angiography and Visconti et al 7,38 using ultra-high frequency ultrasound (UHF-US) allow us to map out the patterns of the perforating vessels in the suprafascial plane preoperatively. When we combine this knowledge with hand-held acoustic Doppler and/or duplex ultrasound, we have high confidence in the anatomical disposition of the vessels in our flaps.…”
Section: Discussionmentioning
confidence: 99%
“…This improves flap survival and shortens operating time. 7,37,38 It also allows us to have thinner flaps, which are more suitable for extremity or head and neck reconstruction, and have lower donor site morbidity. These flaps combined with super-microsurgical techniques, 39 which allow us to anastomose ever smaller vessels (in general under 0.8 mm in diameter), improve our reconstructive options and lead to better outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation